PROJECT-BASED LEARNING PERFORMANCE MEASUREMENT USING VIKOR METHOD AND RANK ORDER CENTROID - Irmansyah Lubis, Ahmadi; Supardianto, Supardianto; Santiputri, Metta; Ardi, Noper; Uperiati, Alena (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Project-Based Learning is a type of learning that is quite widely recommended today, especially in vocational type institutions where the learning is effective in the aim of involving students with direct learning content. The process of evaluating project-based learning on project teams in the performance assessment of each team to rank the order of best performance of all teams is still assessed based on subjective assessments. To overcome these problems, in this study the performance measurement of the project-based learning team by applying the VIKOR method and Rank Order Centroid in conducting assessments with test samples, namely in the Introduction to Database course. The test results obtained based on the calculation of VIKOR and Rank Order Centroid, namely PBL-TRPL01 Team 1 as the best alternative by obtaining based on variations of testing the VIKOR index value with values v=0.4, v=0.5, and v=0.6. Thus, it can be seen that the VIKOR and Rank Order Centroid methods can be applied to the calculation process of measuring team performance in project-based learning.            Keywords: decision Support System; project-based learning; rank order centroid; VIKOR Abstrak: Pembelajaran Berbasis Proyek merupakan jenis pembelajaran yang cukup banyak direkomendasikan di masa kini khususnya pada institusi berjenis vokasional. Pembelajaran tersebut efektif dalam tujuan melibatkan para peserta didik dengan konten pembelajaran secara langsung. Proses evaluasi pembelajaran berbasis proyek pada tim proyek dalam penilaian performa dari masing-masing tim untuk memeringkatkan urutan performa terbaik dari seluruh tim masih dinilai berdasarkan penilaian secara subyektif. Untuk mengatasi persoalan tersebut, pada penelitian ini pengukuran performa tim project-based learning dengan menerapkan metode VIKOR dan Rank Order Centroid dalam melakukan penilaian dengan sampel pengujian yaitu pada mata kuliah Pengantar Basis Data. Hasil pengujian yang diperoleh berdasarkan perhitungan VIKOR dan Rank Order Centroid yaitu bahwa alternatif PBL-TRPL01 Tim 1 sebagai alternatif terbaik dengan peroleh berdasarkan variasi pengujian nilai indeks VIKOR. Maka dengan demikian, dapat diketahui bahwa metode VIKOR dan Rank Order Centroid dapat diterapkan pada proses perhitungan pengukuran performa tim pada pembelajaran berbasis proyek. Kata kunci: pembelajaran berbasis proyek; rank order centroid; sistem pendukung keputusan; VIKOR